On Experience and Thinking to Come in the Late Schelling - Gelžinytė, Brigita (Problemos, 2023)
This paper discusses late Schelling’s concept of experience and its significance regarding the relationship between thought and reality as presented in his Berlin lectures. The question is raised as to what extent his proposed transformation of the modern concept of experience is important for questioning the future of the contemporary philosophical discourse in the context of the “inaccessibility of experience,” as proposed by Benjamin and Agamben. The text argues that, instead of grounding the possibility of experience in the immanent or transcendental forms of subjectivity, the Schellingian alternative allows rethinking experience from the perspective of a radical future. By emphasizing the ontological dimension of experience, its inherent relationship with the question of freedom, and the problem of facticity of thinking itself, it becomes possible to place experience beyond the subject-object relation, immediacy, or sensory and objective cognition. This, it is also argued, allows us to reconsider the role of experience for metaphysics in the light of both post-Kantian and post-idealist forms of self-consciousness.
Keywords: experience; future; reality; facticity; concept; freedom